TRANSESTERIFICATION OF DEGUMMED PALM OIL (DPO) TO PRODUCE PALM BIODIESEL BY USING LIPOZYME TL IM AS BIOCATALYST - Aira Darusmy; Nur Sri Rahayu; Renita Manurung (Jurnal Teknik Kimia USU, 2015)
Biodiesel is usually synthesis ​​by transesterification of triglycerides and alcohols in the presence of an acid or an alkaline catalyst but it could produce a chemical waste process. An alternative process is using biocatalyst such as enzyme to synthesis biodiesel that couldn’t produce chemical waste process. In this research, the synthesis of biodiesel from degummed palm oil (DPO) and methanol as acyl donor has been investigated with using of Lipozyme as biocatalyst. The purpose of this experiment is to examine the effect of the temperature and the amount of biocatalyst for the synthesis of biodiesel that produced from palm oil and examine the effect of the use of methanol to the lipase enzyme activity in catalyzing the synthesis of biodiesel through transesterification reaction. The variables in this research are the amount of biocatalyst and temperature, and their responses with yield conversion of biodiesel are representated using response surface methodology (RSM) with Minitab software. The reactants and products are analyzed using Gas Chromatography Mass Spectrometry (GCMS). Yield raging from 10-79 % are achieved in 15 hours reaction time. The variable effect of process for obtaining yield can be known from the temperature gives negative result about 0,6738 for the formation of biodiesel product. Afterwards the amount of biocatalyst gives positive result about 22,8091 and interaction between temperature and the amount of biocatalyst give negative result. The results show that the most influential variable is the amount of biocatalyst. Therefore, this experiment would need further investigation works and analysis and reuse of lipozyme as biocatalyst on the run which obtained the highest yield. The highest yield is obtained at a reaction temperature of 45 ° C and the amount of catalyst by 30%. In the reuse of lipozyme, can be repeated four times and obtained the total of the decrease in yield of 77%.